Expediente (Revista de Educação Pública, 2014)
Reitora • ChancellorMaria Lúcia Cavalli NederVice-Reitor • Vice-ChancellorJoão Carlos de Souza MaiaCoordenadora da EdUFMT • EdUFMT’s CoordinatorLúcia Helena Vendrúsculo Possari